2023
DOI: 10.3389/fevo.2023.1151182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photovoltaic power station construction on terrestrial ecosystems: A meta-analysis

Abstract: The rapid increase in construction of solar photovoltaic power stations (SPPs) has motivated ecologists to understand how these stations affect terrestrial ecosystems. Comparing study sites, effects are often not consistent, and a more systematic assessment of this topic remains lacking. Here, we evaluated the effects of SPP construction on carbon emissions, edaphic variables, microclimatic factors and vegetation characteristics in a meta-analysis. We employed log response ratios (as effect sizes) to assess ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…Regions with high horizontal solar radiation exhibited more significant positive responses to the construction of PV power stations (Figure 9). This study revealed that the impact of PV power station construction on vegetation characteristics was significant, which is consistent with previous subgroup and correlation analyses [9]. The climatic zone, altitude, ecosystem type, soil depth, solar radiation intensity, and time since PV construction exert considerable influence on the vegetation and soil factors under the PV array.…”
Section: Effects Of Photovoltaic Power Stations On Different Factorssupporting
confidence: 90%
See 3 more Smart Citations
“…Regions with high horizontal solar radiation exhibited more significant positive responses to the construction of PV power stations (Figure 9). This study revealed that the impact of PV power station construction on vegetation characteristics was significant, which is consistent with previous subgroup and correlation analyses [9]. The climatic zone, altitude, ecosystem type, soil depth, solar radiation intensity, and time since PV construction exert considerable influence on the vegetation and soil factors under the PV array.…”
Section: Effects Of Photovoltaic Power Stations On Different Factorssupporting
confidence: 90%
“…Overall, the PV power stations enhanced the soil conditions and vegetation diversity. Additionally, changes in soil conditions and vegetation diversity may vary with environmental influences, such as ecosystem type [9]. Lambert et.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some studies have shown a cooling effect of PV power plants on LST [20][21][22][23], others have reported warming effects [12,24,25]. These inconsistent results may stem from the fact that these local-scale studies differ in the time data collected, as well as in the climate and ecosystem types in which the studies took place [26,27]. Furthermore, because of a lack of long-term monitoring data, it is difficult to compare temperatures near PV plants with pre-construction conditions [22,25,28].…”
Section: Introductionmentioning
confidence: 99%